Ion-Pair Formation of [CoIII(pn)2(Cl)(L)2+.....I-] by Aqueous-Organic Solvent Medium Enhanced Photoreduction: A Perspective Regression Analysis - Stephen, L. Devaraj; Gunasekaran, S.G.; Soundarrajan, M. (Asian Journal of Chemistry, 2020)
Reduction of CoIII centre in CoIII(pn)2(Cl)(L)2+ with reference to solvent medium and structure of the complex via ion pair charge transfer (IPCT) paves way for the novel reaction mechanism route. In this work, we prepared, characterized and photoinduced the complexes CoIII(pn)2(Cl)(L)2+ (where L = RC6H4NH2, R = m-OMe, p-F and H) in the presence of iodide ion. Quantum yield for 254 nm excitation of CoIII(pn)2(Cl)(L)2+ (where L = RC6H4NH2, R = m-OMe, p-F and H) in water-1,4-dioxane mixtures (Diox = 0, 5, 10, 15, 20, 25, and 30% (v/v)) were also derived for all the complexes in presence of added iodide ion, in which CoIII was reduced via [CoIII(pn)2(Cl)(L)2+….. I–] ion-pair formation. The photoinduced state is ion-pair charge transfer transition state and the quantum efficiency is solvent reliant and they are non-reactive. That is, change in ΦCo(II) is dependable with observed increase in xDiox of the mixed solvent medium. Correlation analysis using empirical parameters εr, Y, ETN and DNN provides a model to understand the solvent medium participation and interaction. This work gains an insight into the role of aqueous-organic solvent medium in CoIII(pn)2(Cl)(L)2+ photoreduction, which may be of great significance in developing novel approaches in the field of high performance catalysis.